A study to evaluate post operative drop in serum albumin level as marker for surgical stress and predictor for clinical outcome in laparotomy patients - Sushma, P.; Kumar, J. Pavan; Bhargavi, M. L. (International Surgery Journal, 2022)
Background: Surgical involvements trigger metabolic stress responses of different magnitude, contributing to delayed recovery, complication rate and length of hospital stay. Insulin resistance, serum albumin levels, cytokines such as interleukin-6, interleukin-10, and other cytokines are used in clinical studies as measure for surgical stress. Clinical practitioners routinely measure C-reactive protein (CRP) levels in the blood after surgery to assess postoperative inflammation and predict the likelihood of postsurgical side effects. The slow kinetics of CRP, which makes it a poor predictor of stress-related complications, is a significant drawback. Albumin is widely used as nutritional marker and predictor. It shows an immediate response to surgical stress and could therefore qualify to measure surgical stress and to predict a complicated postoperative course. The aim of the present study was therefore to evaluate post-operative drop in serum albumin as a marker for surgical stress and predictor for clinical outcome in laparotomy patients. Methods: Patients admitted under surgical units from December 2020 to June 2022, at Mamata Medical College and Hospital, Khammam. A study was carried out on 50 patients admitted, undergoing Laparotomy electively and Emergency. All these patients have been assessed both preoperatively and postoperatively and their complications have been documented. Results: Serum albumin levels were compared pre-operatively and postoperatively using analysis of variance (ANOVA) test. There is statistical significance between pre-operative serum albumin levels and postoperative serum albumin levels from post-operative day (POD) 1 to POD 5. Conclusions: The serum albumin measurement is simple, cost effective and easy to perform. Using the serum albumin as a marker, reliable predictions can be made regarding the surgical complications, duration of stay in the hospital and the severity of surgical stress.